Modulation of polyunsaturated fatty acid biosynthesis by antipsychotic medications: implications for the pathophysiology and treatment of schizophrenia. (December 2009) - McNamara, Robert K
Polyunsaturated fatty acids (PUFAs) are a critical component of cellular membranes and modulate multiple signaling pathways required for normal brain development. PUFA acquisition requires dietary intake as well as biosynthesis mediated by desaturase and elongase enzymes, and polymorphisms within these genes can significantly influence PUFA biosynthesis. Substantial evidence suggests that schizophrenia is associated with a dysregulation in PUFA homeostasis, and medication-naive, first-episode psychotic patients exhibit PUFA deficits consistent with impaired PUFA biosynthesis. An emerging body of evidence from in vitro, rodent and clinical trials suggests that antipsychotic medications upregulate PUFA biosynthetic gene expression, enzymatic activity and membrane PUFA composition. Augmentation of PUFA biosynthesis may partly contribute to the therapeutic efficacy of antipsychotic medications, whereas the parallel augmentation of other lipogenic genes may contribute to hyperlipidemia and metabolic dysregulation. These and other data support additional research into the potential role of PUFA biosynthesis in the pathophysiology and treatment of schizophrenia.